DEVELOPING SKILLS IN SOLVING ECONOMIC PROBLEMS THROUGH MATHEMATICAL MODELING - Javlon Fayziev; Alisher Omonov; Oltinbek Mirzamurodov (Bright Mind Publishing, 2025)
This article explores the theoretical and practical foundations of developing skills for solving economic problems through mathematical modeling. Mathematics plays a critical role in analyzing, forecasting, and making decisions in modern economics. Mathematical modeling enables the representation and study of complex economic phenomena using equations and formal structures. The article examines the importance of integrating mathematical modeling into economics education, effective methods for developing analytical skills among students, and the application of these skills in practice. Additionally, it analyzes the current state of economic education in Uzbekistan and presents proposals for improving the effectiveness of mathematical approaches in this field.
Keywords: Mathematical modeling, economic problems, education process, analytical skills, economic analysis, decision-making, applied mathematics, economics education, methodological approaches, Uzbekistan.